Visualization: a tool to study nodes in multi-dimensional networks - Noor, Fozia; Akram, Muhammad Usman; Shah, Asadullah; Khan, Shoab Ahmad (Springer, 2019)
The world of data has become progressively complex with this explosive growth of the web and social networks. The use of complicated multi-dimensional models for such data has made visualization and analysis of data challenging. The multiple dimensions of data contain valuable information, but it is hard to analyze as the information is scattered among the dimensions. Sophisticated appropriate visualization of such networks can help in extracting the networks and node characteristics to improve decision making. The papers study different multi-dimensional data set visualization tool to explore the different ways that can be used to study node characteristics.